CORRELATION BETWEEN CYSTATIN C TO SEVERITY DISEASE OF CIRRHOSIS BASED ON MODEL OF END STAGE LIVER DISEASE SCORE - Heribertus Gunadi; Putut Bayupurnama; Siti Nurdjanah (Faculty of Medicine Universitas Gadjah Mada, 2011)
ABSTRACTBackground: Cirrhosis patients with renal failure are at high risk for death and reduced survival as compared with those without renal failure, and have poor prognosis. Some studies have suggested that cystatin C did more accurate than creatinine /0 detect glomerulusfiltration rate (GFR) in patients with cirrhosis. Model of End Stage Liver Disease (MELD) score can be used in patients with cirrhosis with variously Widely severity disease and etiologies. Until nmv, there is no study about correlation between levels of cystatin C to disease severity in cirrhosis based on MELD score.Objective: This present study was to investigate the correlation between levels of cyst at ill C with disease severity in cirrhosis based on MELD score.Method: Study design was cross sectional s t u d y, This study was conducted at Gastoenterohepatology outpatient clinic and Internal Medicine ward of Dr Sardjito General Hospital, Yogyakarta. Inclusion criteria were patients with cirrhosis diagnosed by clinical criteria, laboratory and USG.findillg, age > 18 years, had complete medical record and obtained informed consent. Exclusion criteria were chronic kidney disease, sepsis, hepatocellutare carcinoma, used high doses of steroid, had thyroid dysfunction. hypertension and diabetes mellitus.Result: The mean of cystatin C based on categorical MELD score were MELD <10 = 0.93±0.19 mgll; MELD IO-19=1.08±0.26 mg/l; MELD 20-29 = 1.25±O.27 mgll; MELD 30-39 = 2.49 mg/l and MELD >40 = 2.43 mgll; 0)=0.013; 95% CI 0.000-0.061). There was a significant correlation between cystatin C to MELD score as demonstrated byp=O.OOOand r=0.485.Conclusion: Our data suggested a significant correlation with medium strength between cystatin C to severity disease of cirrhosis based 011 MELD score. Keywords: cirrhosis, cystatin C, MELD score